A comparison of the sports safety policies and practices of community sports clubs during training and competition in northern Sydney, Australia. Issue 1 (29th January 2004) - Donaldson, A; Forero, R; Finch, C F; Hill, T
Abstract : Objectives: To compare the safety policies and practices reported to be adopted during training and competition by community sports clubs in northern Sydney, Australia. Methods: This cross sectional study involved face to face interviews, using an 81 item extensively validated questionnaire, with representatives of 163 community netball, rugby league, rugby union, and soccer clubs (response rate 85%). The study was undertaken during the winter sports season of 2000. Two separate 14 item scales were developed to analyse the level of safety policy adoption and safety practice implementation during training and competition. The statistical analysis comprised descriptive and inferential analysis stratified by sport. Results: The reliability of the scales was good: Cronbach's α = 0.70 (competition scale) to 0.81 (training scale). Significant differences were found between the safety scores for training and competition for all clubs (mean difference 11.2; 95% confidence interval (CI) 10.0 to 12.5) and for each of the four sports: netball (mean difference 14.9; 95% CI 12.6 to 17.2); rugby league (mean difference 10.3; 95% CI 7.1 to 13.6); rugby union (mean difference 9.4; 95% CI 7.1 to 11.7); and soccer (mean difference 8.4; 95% CI 6.5 to 10.3). Conclusions: The differences in the mean competition and training safety scores were significant for all sports. This indicates that safety policies were less often adopted and practices less often implemented during training than during competition. As injuries do occur at training, and sports participants often spend considerably more time training than competing, sporting bodies should consider whether the safety policies and practices adopted and implemented at training are adequate.